APPLICATION OF ESTRUS SYNCHRONIZATION USING PGF2 AND OVULATION SYNCHRONIZATION USING hCG FOR ARTIFICIAL INSEMINATION OPTIMIZATION ON ONGOLE (PO) BREED CATTLE - Mutmainnah, Mutmainnah; Amrozi, Amrozi; Tumbelaka, Ligaya ITA (Universitas Syiah Kuala, 2017)
This study aimed to determine the pregnancy percentage of Ongole (PO) breed cattle by estrus synchronization and ovulation synchronization. This study used 22 cattle that were divided into three groups: Estrus synchronized cattle (K1, n= 5); ovulation synchronized heifers using ovsynch (K2, n= 6); and ovulation synchronized cow using ovsynch (K3, n= 11). Parameters measured were diameter of corpus luteum (CL) in estrus synchronization, follicular diameter upon synchronization and artificial insemination (AI), and percentage of pregnant cattle. Data obtained were statistically analyzed using analysis of variance followed by Duncan test. Results showed no significant differences (P0.05) of CL diameter at the time of estrus synchronization in all groups of cattle with an average of 16.633.79 mm. The CL diameter at the time of estrus synchronization was not significantly different among groups, with an average of 8.80 2.07 mm. Diameter of follicles during ovulation synchronization was also not significantly different among groups. The average diameter of follicles was 9.012.05 mm. Diameter of follicles at the time of estrus and ovulation synchronization was not significantly different among groups with an average diameter of follicles of 10.942.10 mm. The pregnancy percentage of K1, K2, and K3 were 60%, 16%, and 36%, respectively. There was no correlation between the diameters of follicles during estrus with the pregnancy percentage. Estrus synchronization produced higher pregnancy rate than ovulation synchronization in cow or heifers.